Анализ систем технического зрения мобильных наземных роботов - Ленский, Р. В. (ХНУРЕ, 2019)
Ground mobile robots are designed to perform a wide range of tasks and require an advanced and sophisticated internal navigation and control system to effectively perform the functions assigned to them. An analysis of the literature shows that there are four different technical approaches to the design of technical vision devices for mobile ground robots: methods based on the use of a camera; laser scanning systems; GPS-based methods; ranging devices ranging (based on radar, sonar, laser principles).